Sustainability in university campuses:: a case study of the International Alliance of Research Universities (Sustainability in Debate, 2018)
The concepts of Higher Education Institutions (HEIs) are very much part of the problem as of the solution. Global networks and initiatives support the HEIs engaged in implementing an Environmental Management System (EMS) in their on-campus activities. The objective of this work is to present, in a descriptive and illustrative way, the development of the main sustainability actions in the campuses of HEIs members of an international alliance. A research-oriented application and a solution used for documentary analysis of Sustainability Reports (SR) available online by HEIs members of the International Alliance of Research Universities (IARU). The results describe the development of sustainability actions and illustrate the segments as member HEIs. The conclusions of this research indicate that there are benefits in working in a network, minimizing the environmental impact of the activities practiced on campuses, but that there are other important factors for the management of HEIs to become sustainable and effective.